Importance of climatic data analysis for biodiversity studies in Mediterranean mountains of the Iberian Peninsula - Blanquer Lorite, José Manuel; Gutiérrez Girón, Alba; Gavilán, Rosario G. (Lazaroa, 2014)
Recent studies on climate change and the development of international scientific nets for the observation and analysis of global warming on the biodiversity have had an immediate effect on Ecology labs. It is the case of Enviroclim_lab created to cover all the necessary instrumentation management to collect outdoors bioclimatic data. The analysis of such data is also included in the daily tasks.